Persepsi Masyarakat Terhadap Inovasi Kemasan Produk, Desain Kemasan, dan Harga Produk Gula Aren Serbuk dan Gula Aren Kristal di Kota Kendari - Eduard, Siska Stevin Noviatin; Rianse, Usman; Abdullah, Weka Gusmiarty (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This study aims to (1) Know the public's perception of the price, packaging, brand and label of powdered palm sugar and crystal palm sugar in Kendari City and (2) Know the Priorities for the community related to the price, packaging, brand and label of palm sugar and crystal sugar in Kendari City. The location of this study is Kendari City, precisely at several palm sugar drink outlets. This location was chosen as a deliberate research location, namely (Purposive Sampling), based on consideration of the number of outlets for drinks made from palm sugar. The population is the people of Kendari City who consume powdered palm sugar and crystalline palm sugar. The sampling technique uses the Purposive sampling technique, which is sampling based on data based on the consideration that respondents have bought powdered palm sugar and crystal sugar in Kendari City, the number of samples in this study was as many as 50 respondents who would be spread in Kendari City. The data analysis used in this study is the analysis of consumer perceptions and the analysis of index values. The results showed that (1) Rata-average powdered palm sugar in terms of price, packaging, brand and label is superior to crystal sugar. It can be interpreted that ristal sugar is less attractive to respondents , causing a lack of consumer interest in sugar crystalline and (2) highter riority P for powdered palm sugar is information about the composition/content of the product on the label variables and the lowest priority is the size of the packaging on the packaging varibels while the highest priority crystals are Information about the expiration period on the label variable and the lowest priority is Information about the benefits of the product on varibel labels .